INFLUENCE OF WORK ENVIRIONMENT SERVICE QUALITY AND CORPORATE IMAGE: CASE STUDY BLACK SHEEP COFFEE SHOP IN NAKHONSAWAN PROVINCE - Intrasinghathong, Wiroon; Rangsinan, Winai; Bunpayom, Janyapon; Petkrachang , Chusak (Journal of MCU Nakhondhat, 2023)
The purpose of this study was to study the direct effect and total effect of work environment service quality with corporate image. This study was quantitative research. The samples of this study covered 382 customers of black sheep coffee shop. The convenience sampling technique had been conducted. The research instrument was 5 rating scale questionnaires. The statistics were mean, standard deviation, correlation coefficient, path coefficient, direct effect, indirect effect and total effect. LISREL program 8.80 was applied for analysis. The research results indicated that: The total levels of work environment, service quality and corporate image were at a high level. Work environment had direct effect on service quality statistically significant at .01. (DE = .888, p = .01) It could predict service quality at 78.90 per cent. (R2 = .789). Work environment had direct effect on corporate image statistically significant at .01. (DE = .805, p = .01). It could predict corporate image statistically significant at 64.70 per cent.(R2 = .647). Service quality had direct effect on corporate image statistically significant at .01.(DE = .834, p = .01). It could predict corporate image at 69.00 (per cent. (R2 = .690. Work environment and service quality had total effect on corporate image statistically significant at .01. (TE = .868, p = .01). They could predicted corporate image at 75.30 per cent. (R2 = .753)